MODIFIKASI DESAIN MESIN PENGUPAS KULIT KOPI (HULLER) - Sinaga, Robert; Siregar, Rico Taruna; Zulazmi, Muhammad Fauzan; Ginting, Alwi Okta Jeremy (Universitas Quality, 2024)
This study aims to modify the design of a coffee bean huller machine to enhance the efficiency and quality of the hulling process. The background of this research lies in the importance of agricultural technology development in improving productivity and the quality of agricultural products, particularly in coffee processing. Existing huller machines have several drawbacks such as low hulling efficiency and damage to the coffee beans produced. The methodology employed in this research includes literature review, user needs analysis, conceptual modification design, prototype fabrication, and machine performance testing. Various technical aspects such as machine speed, hulling design, and pressure adjustment mechanisms were considered in the modification process. The results of the study show that modifications to the huller machine design can improve the efficiency of the coffee bean hulling process and reduce bean damage. Performance testing of the machine prototype yielded increase in efficiency compared to conventional huller machines. Additionally, the quality of the coffee beans produced also improved, with lower levels of damage. Thus, the modification of the huller machine design has the potential to enhance productivity and quality in the coffee bean hulling process, contributing positively to agricultural technology development in the coffee plantation sector.